Efficient synergetic combination of H-USY and SnO2 for direct conversion of glucose into ethyl levulinate (Biofuel Additive) - Heda, Jidnyasa; Niphadkar, Prashant; Bokade, Vijay (Energy & Fuels, 2019)
Ethyl levulinate (EL), a biofuel additive for petroleum and biodiesel can also be used as a 100% fuel to replace petroleum diesel with the existing diesel engine. The major problem to make the EL process economical is the lack of a proper conversion technology to convert C-6 sugars such as glucose with higher yield of EL as well as process which can tolerate higher glucose concentration to increase productivity. The present study highlighted the catalytic synthesis of EL from glucose over synergetic combination of zeolite H-USY and Lewis acidic catalysts such as Sn-beta, TiO2, ZrO2, and SnO2. Because of the strong Lewis acidic nature and the subsequent enhancement in the isomerization rate from glucosides to fructosides, the synergetic combination of H-USY with SnO2 showed higher EL yield than the combination with other Lewis acidic catalysts. So far, the highest EL yield of 81% from glucose (50 g/L) at 180 degrees C in 3 h was achieved over the optimal combination of 95% H-USY and 5% SnO2 having strong/weak acidity and B/L ratios of 1.30 and 0.75, respectively. The study was further extended for establishing the proposed reaction mechanism without the formation of 5-hydroxymethyl furfural, levulinic acid, and formic acid which makes the overall process clean and green.

Effect of acidity and mesoporosity in H-USY on conversion of wheat straw to ethyl levulinate (Biofuel additive) - Heda, Jidnyasa; Niphadkar, Prashant; Nandanwar, Sachin; Bokade, Vijay (Journal of the Indian Chemical Society, 2023)
Cold flow properties of biodiesel can be improved by addition of additives especially ethyl levulinate (EL up to 20%). There are very limited information on synthesis of EL from actual raw biomass like wheat straw over heterogeneous catalyst. The present article elaborated on optimization of Acidity to Mesoporosity ratio in H-USY, which is crucial for its application in conversion of raw wheat straw to selective formation of EL in one-step. The acidity and mesoporosity is monitor by systematic post treatment of desilication and dealumination. Optimum acidity/mesoporosity ratio of 3.6 in HUSY resulted in to maximum EL yield of 24.5%, which is probably the highest so far.
Keywords: Acidity; Biofuel additive; Dealumination; Desilication; ethyl levulinate; H-USY; Mesoporosity; Wheat straw